RNA-Scoop: interactive visualization of transcripts in single-cell transcriptomes. (29th November 2021) - Stephenson, Maria; Nip, Ka Ming; HafezQorani, Saber; Gagalova, Kristina K; Yang, Chen; Warren, René L; Birol, Inanc
Abstract: Recent advances in single-cell RNA sequencing technologies have made detection of transcripts in single cells possible. The level of resolution provided by these technologies can be used to study changes in transcript usage across cell populations and help investigate new biology. Here, we introduce RNA-Scoop, an interactive cell cluster and transcriptome visualization tool to analyze transcript usage across cell categories and clusters. The tool allows users to examine differential transcript expression across clusters and investigate how usage of specific transcript expression mechanisms varies across cell groups.